2021
DOI: 10.51437/jgns.v1i1.11
|View full text |Cite
|
Sign up to set email alerts
|

History and Current State of Global Neurosurgery in Sub-Saharan Africa

Abstract: Archaeological sources reported traces of trepanation in ancient Egypt 3000 years ago, and Papyri of that time already describedtechniques for the treatment of head trauma (1). The history of modern neurosurgery in Sub-Saharan Africa (SSA) is recent, and thereare two significant periods to be considered.The first period can be called the pre-independence period. This period corresponded tothe 1950s, when most African nations were still colonized. During this period, neurosurgical care was delivered by surgeons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A randomised controlled trial conducted in Nigeria found that TMS significantly reduced seizure frequency in 40% of patients with refractory epilepsy [16] . Another study conducted in South Africa found that DBS significantly reduced the seizure frequency in patients with refractory epilepsy who had undergone resective surgery [17] . However, these interventions require specialised equipment and trained personnel and may carry risks of adverse events, such as headaches or seizures.…”
Section: Effectiveness Of Nonpharmacological Therapiesmentioning
confidence: 99%
“…A randomised controlled trial conducted in Nigeria found that TMS significantly reduced seizure frequency in 40% of patients with refractory epilepsy [16] . Another study conducted in South Africa found that DBS significantly reduced the seizure frequency in patients with refractory epilepsy who had undergone resective surgery [17] . However, these interventions require specialised equipment and trained personnel and may carry risks of adverse events, such as headaches or seizures.…”
Section: Effectiveness Of Nonpharmacological Therapiesmentioning
confidence: 99%
“…Neurosurgery is a fast-growing medical specialty in Africa ( 1 , 2 ). Africa is disproportionately affected by the high burden of neurosurgical conditions ( 3 ), and the vast majority of African medical students have limited exposure to neurosurgery ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neurosurgical anatomy is highly specific to the human brain and does not compare well with animal specimens. Moreover, the management of cadaveric models entails ethical concerns and high maintenance costs, as well as specific and highly equipped structures for their preservation ( 2 ). Moreover, many anatomists believe a medical student-cadaver relationship is essential in developing surgical skills and in developing proper attitudes toward patients ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%